О зараженности эктопаразитами сизого голубя и кольчатой горлицы в окрестностях Львова - Яворницкий, В.И.; Харамбура, Я.Й. (Вестник зоологии, 1982)
14 collared turtle dove and 36 rock dove specimens from Lvov and Lvov Region were examined for ectoparasitic infestation. Nineparasitic Arthropod specieswere found: ralculter rostratus. Megnina columbae, Dermanyssus gallinae, Bonomiella Hohostiella gigantea, N e o c o l n o c e n n a l u m turotnatum, Campanulotes oidentatus. Coloceras damicorne, Columbicola columbae. The data on population structure, i n t e n s i t ya n d extensity of infestation are given. Illustrated redescription of B. concil, for the first time found in the U S S R is presented.